Analysis of resistance stories of "Mystery of Masih" by Ebrahim Hasanbeigi - Foroozanfar, Ahmad (Opción, 2019)
Structural look at literary works of art provides a better understanding about literary nature and develops literal works of art. The study tries to find the elements within the text and their juxtaposition in the story of "mystery of Masih" with a library methodology, taking notes and analytical method. As a conclusion, this is a narrative story of which process is to move from the initial peace toward the climax and then returning to the peace at the end. Furthermore, we can say that the narrative structure of "mystery of Masih" is adjusted and corresponds with Bremon theory.